Antibacterial Potency and Physicochemical Profiles of Eucalyptus pellita Leaf Waste Essential Oil from PT Surya Hutani Jaya, East Kalimantan - Wartomo, Wartomo; Aryani, Farida; Hernandi, Muhammad Fikri; Rositah, Erna; Ngapiyatun, Sri; Sari, Nur Maulida (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Eucalyptus is one of the fast growing species plants, currently used in the pulp and paper industry. The leaves of Eucalyptus are known as forest harvesting waste. This research aim to examine the antibacterial potency and the physicochemical profiles of Eucalyptus pellita leaves waste essential oils grown in PT Surya Hutani Jaya Site 32, East Kalimantan named EP B077. The essential oils distilled using water and steam distillation methods. Analysis of physicochemical profiles from this oil included yield, colour, refractive index, specific gravity, and chemical compositions by GC-MS. Antibacterial activity assayed by agar diffusion method against Staphylococcus epidermidis, Streptoccoccus sobrinus and Streptoccoccus mutans with slight modification. The results showed that EP B077 had the yellow colour, yield oils was 0.44%, 1.471 of refractive index, and 0.8706 of specific gravity. Chemical components of EP B077 oils were dominated by Î±-Pinene (40.36%), 1-Î²-Pinene (31.75%), Cyclohexene, 1-methyl-4-(1-methylethenyl)- (9.64%), Trans(Î²)-Caryophyllene (4.29%) and Eucalyptol (1,8-Cineole) (3.88%). This EP B077 oils was active to inhibit bacteria against S. epidermidis and S. sobrinus range from 9-15 mm, also against S.mutans ranging from 9-14 mm. Based on the results, this Eucalyptus pellita leaves named EP B077 had potential to develop as a new source of essential oil and antibacterial agents.